SILAR deposited porous polyaniline-titanium oxide composite thin film for supercapacitor application. (September 2016) - Deshmukh, P.R.; Patil, S.V.; Bulakhe, R.N.; Sartale, S.D.; Lokhande, C.D.
Graphical abstract: Highlights: Porous PANI-TiO2 composite nanofibers are synthesized using a successive ionic layer adsorption and reaction (SILAR) method. The PANI-TiO2 composite nanofibers show the maximum specific capacitance of 776 Fg −1 . The PANi-TiO2 composite nanofibers show the higher stability up to 83% over 5000 cycles. Abstract: The present investigation shows the facile preparation of porous polyaniline-titanium oxide composite nanofibers using a successive ionic layer adsorption and reaction (SILAR) method. The result of X-ray diffraction indicates the amorphous nature of polyaniline-titanium oxide (PANI-TiO2 ) composite nanofibers. Fourier transform infrared (FT-IR) and FT-Raman spectroscopy studies reveal the formation of composite material. The morphology of PANI-TiO2 composite observed using scanning electron microscope (SEM) shows the spherical TiO2 nanoparticles grown on the PANI nanofibers. The electrochemical measurement shows PANI-TiO2 composite electrode yields specific capacitance of 776 Fg −1 and gives higher capacitance retention (83%) over 5000 cycles. The superior electrochemical properties attributed to the porous structure of PANI-TiO2 composite nanfibers as well as the synergistic effect between conducting PANI nanofiber and TiO2 nanoparticles. This specifies that this method may provide a promising strategy for preparation of PANI-based transition metal oxide composite thin film electrodes for better performance of supercapcitor.